2017
DOI: 10.1038/s41467-017-00880-2
|View full text |Cite
|
Sign up to set email alerts
|

Extrafollicular CD4+ T-B interactions are sufficient for inducing autoimmune-like chronic graft-versus-host disease

Abstract: Chronic graft-versus-host disease (cGVHD) is an autoimmune-like syndrome mediated by pathogenic CD4+ T and B cells, but the function of extrafollicular and germinal center CD4+ T and B interactions in cGVHD pathogenesis remains largely unknown. Here we show that extrafollicular CD4+ T and B interactions are sufficient for inducing cGVHD, while germinal center formation is dispensable. The pathogenesis of cGVHD is associated with the expansion of extrafollicular CD44hiCD62loPSGL-1loCD4+ (PSGL-1loCD4+) T cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 71 publications
6
79
0
Order By: Relevance
“…GVL models, cGVHD models, T-cell purification, and T-cell depleted bone marrow, antibodies and flow cytometry, in vitro T-cell polarization, in vitro and in vivo mixed lymphocyte reactions, in vitro and in vivo iTreg stability assay, lymphocyte isolation from recipient liver, histological analysis, DNA methylation assay, human Sirt-1 activity assay, and western blotting analysis are described in previously published work [20][21][22][23][24][25][26][27] and are also detailed in the supplemental Methods, available on the Blood Web site.…”
Section: Methodsmentioning
confidence: 99%
“…GVL models, cGVHD models, T-cell purification, and T-cell depleted bone marrow, antibodies and flow cytometry, in vitro T-cell polarization, in vitro and in vivo mixed lymphocyte reactions, in vitro and in vivo iTreg stability assay, lymphocyte isolation from recipient liver, histological analysis, DNA methylation assay, human Sirt-1 activity assay, and western blotting analysis are described in previously published work [20][21][22][23][24][25][26][27] and are also detailed in the supplemental Methods, available on the Blood Web site.…”
Section: Methodsmentioning
confidence: 99%
“…58 T FH are a T-cell subset that has recently been shown to be correlated with cGVHD pathogenesis. 32,34 Although the role of T FH and GC B cells in murine models of cGVHD is still under debate, 29,59 Forcade et al recently indicated a key role of T FH , which strongly correlated with cGVHD in human patients. 33 Accordingly, in our study murine recipients of XBP-1 KO B cells displayed an indirect impact on T FH cell differentiation, where donor T FH cells were reduced in the spleens.…”
Section: Discussionmentioning
confidence: 99%
“…A major role for EF reactions in the generation of pathogenic autoreactive B cells has also been established in other mouse models, including the NZB/W and graft-vs-host models of lupus-like autoimmunity. 59,60 It is important to note that, concordant with human SLE factors, murine lupus can be induced by dysregulation of pathways Other studies, however, suggest that the defining ABC transcription…”
Section: E X Tr Afollicul Ar B-cell Re Ac Ti On S In S Le Model Smentioning
confidence: 99%